The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/0026-7902.00037
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Language Teaching (CLT): Practical Understandings

Abstract: The aim of this article is to report on a study that documented the views and practices of communicative language teaching (CLT) by Japanese second language inservice teachers. Compared to theoretical developments of CLT (e.g., see Savignon, 1991), little is known about what second language teachers actually understand by CLT and how they implement CLT in classrooms. Using multiple data sources including interviews, observations, and surveys, the article reports how teachers defined CLT and implemented it in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
100
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 56 publications
(60 reference statements)
16
100
0
5
Order By: Relevance
“…These findings support those reported by Hickmann (2001) that academic difficulties result in an advocacy for second language instruction. This is also the reason why Sato and Kleinsasser (1999) argue that it is a mistake to underestimate the role of the L1 in the teaching and learning of an L2, and the dogmatic use of the target language may increase the learners' stress, frustration and embarrassment.…”
Section: Constraints On the Implementation Of The Monolingual Apmentioning
confidence: 99%
“…These findings support those reported by Hickmann (2001) that academic difficulties result in an advocacy for second language instruction. This is also the reason why Sato and Kleinsasser (1999) argue that it is a mistake to underestimate the role of the L1 in the teaching and learning of an L2, and the dogmatic use of the target language may increase the learners' stress, frustration and embarrassment.…”
Section: Constraints On the Implementation Of The Monolingual Apmentioning
confidence: 99%
“…Another study involving ten teachers of Japanese in Queensland state schools (Sato & Kleinsasser, 1999), found that teachers' conceptions of CLT were of four types: (a) CLT is about learning to communicate in the second language; (b) CLT uses mainly speaking and listening; (c) CLT involves little grammar instruction; and (d) CLT uses activities that are time consuming. Observation of classroom practices in this study also indicated that teachers tended to use a didactic approach, with grammar playing a central role, features not consistent with CLT approaches.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Rather than having a single, straightforward and linear relationship between L2 students' attitudes and teachers' beliefs, we can form a picture which is much more complicated (Borg, 2006;Li, 2008;Sato, & Kleinsasser, 2004).…”
Section: Resultsmentioning
confidence: 99%